2021
DOI: 10.1021/acs.inorgchem.1c01399
|View full text |Cite
|
Sign up to set email alerts
|

Reductions of M{N(SiMe3)2}3 (M = V, Cr, Fe): Terminal and Bridging Low-Valent First-Row Transition Metal Hydrido Complexes and “Metallo-Transamination”

Abstract: The reaction of the vanadium(III) tris(silylamide) V{N(SiMe 3 ) 2 } 3 with LiAlH 4 in diethyl ether gives the highly unstable mixed-metal polyhydride [V(μ 2 -H) 6 [Al{N(SiMe 3 ) 2 } 2 ] 3 ]-[Li(OEt 2 ) 3 ] (1), which was structurally characterized. Alternatively, performing the same reaction in the presence of 12-crown-4 affords a rare example of a structurally verified vanadium terminal hydride complex, [VH{N(SiMe 3 ) 2 } 3 ][Li(12-crown-4) 2 ] (2). The corresponding deuteride 2D was also prepared using LiAlD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…For the case of the 3 + charged cations; the Cr(III) (0.69A ionic radius) showed higher Qe than Fe(III) (0.64 A ionic radius). Without being conclusive, there is an apparent relationship between the possible size of the cation and Qe; this could imply that cations with ionic radius approaching to 1A have greater susceptibility to generate interactions with the hydrophilic functional groups present in the polymeric chains of the HEMA/DMAa membranes; apparently, the size of the cation is determinant, as has been argued in previous reports [48][49][50][51].…”
Section: Sorption Equilibriummentioning
confidence: 87%
“…For the case of the 3 + charged cations; the Cr(III) (0.69A ionic radius) showed higher Qe than Fe(III) (0.64 A ionic radius). Without being conclusive, there is an apparent relationship between the possible size of the cation and Qe; this could imply that cations with ionic radius approaching to 1A have greater susceptibility to generate interactions with the hydrophilic functional groups present in the polymeric chains of the HEMA/DMAa membranes; apparently, the size of the cation is determinant, as has been argued in previous reports [48][49][50][51].…”
Section: Sorption Equilibriummentioning
confidence: 87%
“…[Na 2 Mg 2 {N(Pr i ) 2 } 4 (μ-H) 2 •(toluene) 2 ]) originally reported by Mulvey and co-workers. 56 We recently reported that the donor solvent-free iron/lithium inverse crown could be prepared by reaction of Fe{N(SiMe 3 ) 2 } 3 with lithium aluminum hydride, 33 and the isolation of titanium/ sodium 3 further highlights that this structural motif is likely accessible for a variety of metals. The structure of 3 suggests that the reduction of [Ti(μ-Cl){N(SiMe 3 ) 2 } 2 ] 2 (1) with sodium metal may transiently form a divalent "Ti{N-(SiMe 3 ) 2 } 2 " species that then subsequently reacts with ligand CH moieties to form the hydride complex 3.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…A coordination chemistry was initiated for the titanium and vanadium tris­(silylamide) complexes (previously thought not possible due to steric crowding) to give M­{N­(SiMe 3 ) 2 } 3 L 2 (L = a nitrile or isocyanide ligand) complexes . Additionally, the isolation of a new vanadium­(V) oxy silylamide complex, e.g., V­(=O)­{N­(SiMe 3 ) 2 } 3 , that was absent from the literature despite several attempts to isolate it, and the synthesis of several unusual metal hydride complexes that are available by reduction of M­{N­(SiMe 3 ) 2 } 3 complexes were described …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ln–N­(κ 3 -Tp) bond distances in 2-Ln are consistent with those of 1-Ln and [Ln­(Tp) 2 ] + in the literature . The Al–N­(N″) bond distances of 1.8430(19)–1.844(3) Å in 2-Ln are similar to those in [ V ] [1.837(2) Å], TM/Al heterobimetallic hydrides containing TM–(μ-H) 2 –Al­(N″) n , and the homoleptic complex [Al­(N″) 3 ] [1.813(3) Å] …”
mentioning
confidence: 99%